Is lean mass quantity or quality the determinant of maximal fat oxidation capacity? The potential mediating role of cardiorespiratory fitness - Edgardo Opazo-Díaz; Juan Corral-Pérez; Alejandro Pérez-Bey; Alberto Marín-Galindo; Adrián Montes-de-Oca-García; María Rebollo-Ramos; Daniel Velázquez-Díaz; Cristina Casals; Jesús-Gustavo Ponce-González (Journal of the International Society of Sports Nutrition)
Background Impaired fat oxidation is linked to cardiometabolic risk. Maximal fat oxidation rate (MFO) reflects metabolic flexibility and is influenced by lean mass, muscle strength, muscle quality – defined as the ratio of strength to mass – and cardiorespiratory fitness. The relationship between these factors and fat oxidation is not fully understood. The aim is to analyze the associations of lean-mass, muscle strength and quality with fat oxidation parameters in young adults, considering the mediating role of VO2max.Methods A cross-sectional observational study. Eighty-one adults (50 males, 31 females; age 22.8 ± 4.4, BMI 25.70 ± 5.75, lean-mass 54.19 ± 8.78, fat-mass 18.66 ± 11.32) Body composition assessment by bioimpedance determine fat and lean-mass. Indirect calorimetry at rest and exercise was used for the calculation of fat oxidation. An incremental exercise protocol in a cycle ergometer with two consecutive phases was performed. The first to determine MFO consisted of 3 min steps of 15W increments with a cadence of 60rpm. The test was stopped when RQ ≥ 1. After 5 min rest, a phase to detect VO2max began with steps of 15W/min until exhaustion. Muscular strength was assessed by handgrip dynamometry and the standing longitudinal jump test. A strength cluster was calculated with handgrip and long jump adjusted by sex and age. Data were analyzed using multiple linear regression and mediation analyses.Results Total lean-mass and leg lean-mass were not associated with MFO. Long jump, relativized by lean-mass and by leg lean-mass have a standardized indirect effect on MFO of 0.50, CI: 0.32–0.70, on MFO/lean-mass 0.43, CI:0.27–0.60 and MFO/leg lean-mass 0.44, CI: 0.30–0.06, which VO2max mediated, VO2max/lean-mass and VO2max/leg lean-mass, respectively (all p < 0.01). The handgrip/arm lean-mass had an indirect effect of 0.25 (CI: 0.12–0.38) on MFO/leg lean-mass, with VO2max/leg lean-mass as the mediator (p < 0.01). The Cluster/lean-mass and Cluster/Extremities lean-mass have a standardized indirect effect on MFO/lean-mass (0.34, CI: 0.20–0.48) and MFO/leg lean-mass (0.44, CI: 0.28–0.60), mediated by VO2max/lean-mass and VO2max/leg lean-mass (p < 0.01).Conclusions Muscular strength and quality have an indirect effect on MFO mediated by VO2max. These findings suggest the importance of muscle quality on MFO.